Didactic aspects of сase-study technologу use in training skilled workers of agrarian profile - Slatvinska, O (Professional Pedagogics, 2011)
A unique feature of сase-study method is a creation of problem situation from real life. The useof сase-study method while teaching a number of subjects to students of agrarian profile vocationalschools will enable to intensify cognitive interest to studies, will promote the advance of research,communicative and creative skills of future agrarians.
Keywords: educational process, сase-study method